2021
DOI: 10.3389/fvets.2021.692646
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors Associated With Antimicrobial Resistance in Bacteria Related to Bovine Respiratory Disease—A Broad Cross-Sectional Study of Beef Cattle at Entry Into Canadian Feedlots

Abstract: A broad, cross-sectional study of beef cattle at entry into Canadian feedlots investigated the prevalence and epidemiology of antimicrobial resistance (AMR) in Mannheimia haemolytica, Pasteurella multocida, Histophilus somni, and Mycoplasma bovis, bacterial members of the bovine respiratory disease (BRD) complex. Upon feedlot arrival and before antimicrobials were administered at the feedlot, deep nasopharyngeal swabs were collected from 2,824 feedlot cattle in southern and central Alberta, Canada. Data on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 69 publications
(113 reference statements)
4
15
2
Order By: Relevance
“…The strongest correlation is between H. somni and M. bovis bacteria. This correlation was also shown by Andrés-Lasheras et al [ 2 ]. The next one shown between bacteria also occurred with M. bovis , but it had the lowest strength of effect of a given association and it was the correlation with M. haemolytica .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The strongest correlation is between H. somni and M. bovis bacteria. This correlation was also shown by Andrés-Lasheras et al [ 2 ]. The next one shown between bacteria also occurred with M. bovis , but it had the lowest strength of effect of a given association and it was the correlation with M. haemolytica .…”
Section: Discussionsupporting
confidence: 85%
“…What it means is that M. haemolytica was significantly less frequent with concurrent BRSV, but this relationship is at the limit of statistical significance, with a low strength of effect. A study of Canadian cattle by Andres-Lasheras et al showed a correlation in cattle between M. haemolytica and H. somni and between P. multocida and M. bovis [ 2 ]. In our study, correlations between these pathogens were not detected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of resistance to macrolides in M. bovis were detected in our study, in agreement to previous reports (30,65). A western Canadian study reporting on resistance rates of M. bovis recovered from feedlot cattle also demonstrated elevated macrolide-resistance rates, with resistance to various macrolides detected in over 95% of isolates (55).…”
Section: Figure 3 |supporting
confidence: 92%